Influence of DC magnetron sputtering reaction gas on structural and optical characteristics of Ce-oxide thin films - Miran, H.; Jiang, Z.; Altarawneh, M.; Veder, Jean-Pierre; Zhou, Z.; Rahman, M.; Jaf, Z.; Dlugogorski, B. (Elsevier Science Ltd, 2018)
The influence of the reaction gas composition during the DC magnetron sputtering process on the structural, chemical and optical properties of Ce-oxide thin films was investigated. X-ray diffraction (XRD) studies confirmed that all thin films exhibited a polycrystalline character with cubic fluorite structure for cerium dioxide. X-ray photoelectron spectroscopy (XPS) analyses revealed that cerium is present in two oxidation states, namely as CeO2and Ce2O3, at the surface of the films prepared at oxygen/argon flow ratios between 0% and 7%, whereas the films are completely oxidized into CeO2as the aforementioned ratio increases beyond 14%. Various optical parameters for the thin films (including an optical band gap in the range of 2.25–3.1 eV) were derived from the UV–Vis reflectance. A significant change in the band gap was observed as oxygen/argon flow ratio was raised from 7% to 14% and this finding is consistent with the high-resolution XPS analysis of Ce 3d that reports a mixture of Ce2O3and CeO2in the films. Density functional theory (DFT+U) implemented in the Cambridge Serial Total Energy Package (CASTEP) was carried out to simulate the optical constants of CeO2clusters at ground state. The computed electronic density of states (DOSs) of the optimized unit cell of CeO2yields a band gap that agrees well with the experimentally measured optical band gap. The simulated and measured absorption coefficient (a) exhibited a similar trend and, to some extent, have similar values in the wavelength range from 100 to 2500 nm. The combined results of this study demonstrate good correlation between the theoretical and experimental findings.